Analisis Peran Serta SPEK-HAM Dalam Proses Pendampingan Kasus KDRT di Surakarta (Perkara Putusan PA Surakarta Nomor 241/Pdt.G/2023/PA.Ska) (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Human rights violations such as domestic violence (DV) remain a major issue in Indonesia. Providing support to DV victims is one way to combat the problem of domestic violence. Solidarity Women for Humanity and Human Rights (SPEK-HAM) is one organization that assists domestic violence victims. The aim of this research is to examine how SPEK-HAM helps domestic violence cases in Surakarta. This study uses a qualitative sociological legal research method. Interviews, observations, and document analysis are the data collection methods used. The findings of this study indicate the importance of SPEK-HAM's role in supporting decisions made in the case of PA Surakarta Number 241/Pdt.G/2023/PA.Ska involving domestic violence. SPEK-HAM's responsibilities include legal assistance, which helps domestic violence victims obtain justice through the legal system; psychological assistance, which involves helping domestic violence victims regain their psychological health; and social assistance, which helps domestic violence victims meet their daily needs..